Pengaruh Model Inkuiri Terbimbing dan Keterampilan Proses Sains terhadap Hasil Belajar Kognitif Siswa pada Mata Pelajaran IPA - Amat, Amat; Haritani, Hartini; Wazni, M. Khairul (JOEAI (Journal of Education and Instruction), 2022)
This study aims to determine whether the influence of guided inquiry learning models and pro-science skills on the cognitive learning outcomes of grade V science students. This type of research is Quasi-Experimental research with a research design using T treatment by Level 2x2. The population in this study were grade V students of elementary school. This research instrument is a multiple-choice test with a total of 20 questions. Data processing techniques and data analysis are descriptive statistics and infrencial statistics with SPSS 22. The data analysis results show significant differences in student cognitive learning outcomes with guided inquiry methods and science process skills, namely sig. = 0.000 < 0.05, meaning that there are differences in learning outcomes taught by guided inquiry (experimental class) with student learning outcomes taught by conventional approaches (control classes). Furthermore, there is an interaction caused between the use of guided inquiry methods by looking at the level of skills of the student's science process towards the cognitive learning outcomes. This can also be proven from the hypothesis test results, namely with a value of sig. = 0.000 < 0.05 means that there is a significant interaction between the use of guided inquiry and the skill level of the student's science process to influence the cognitive learning outcomes of students together. The conclusion of this study is that there is no significant interaction between science process skills and learning outcomes. The cognitive learning outcomes of students who were taught using the guided inquiry learning model were higher than those taught using the conventional learning model for students with low science process skills. Keywords: Guided Inquiry, Learning Outcomes, Process Skills